Analysis Of The Level Of Consumer Satisfaction With Product Quality Attributes And Service Quality Of Fresh Fruit Shopping In Modern Markets In Ambon City (Case Study Of Hypermart Maluku City Mall). - Vika Krisanda Wenno; Leunard O. Kakisina; Maisie T. F. Tuhumury (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the level of consumer satisfaction with product quality attributes and service quality of fresh fruit shopping at the Ambon City Modern Market. The sample of this study is 100 consumers who happen to shop for fresh fruit at Hypermart Maluku City Mall. There are 2 methods used to analyze data, namely the Customer Satisfaction Index method and the Importance Peformance Analysis (IPA) method. The results of the study show that the level of consumer satisfaction with the attributes of fresh fruit at Hypermart Maluku City Mall, is in the very satisfied category, which is 0.81-1.00.